Mechanisms of evasive resistance to anti-VEGF therapy in glioblastoma - Lu, Kan V (Future Medicine Ltd, 2013)
Angiogenesis inhibitors targeting the VEGF signaling pathway have been US FDA approved for various cancers including glioblastoma (GBM), one of the most lethal and angiogenic tumors. This has led to the routine use of the anti-VEGF antibody bevacizumab in recurrent GBM, conveying substantial improvements in radiographic response, progression-free survival and quality of life. Despite these encouraging beneficial effects, patients inevitably develop resistance and frequently fail to demonstrate significantly better overall survival. Unlike chemotherapies, to which tumors exhibit resistance due to genetic mutation of drug targets, emerging evidence suggests that tumors bypass antiangiogenic therapy while VEGF signaling remains inhibited through a variety of mechanisms that are just beginning to be recognized. Because of the indirect nature of resistance to VEGF inhibitors there is promise that strategies combining angiogenesis inhibitors with drugs targeting such evasive resistance pathways will lead to more durable antiangiogenic efficacy and improved patient outcomes. Further identifying and understanding of evasive resistance mechanisms and their clinical importance in GBM relapse is therefore a timely and critical issue.